T cell receptor recognition of hybrid insulin peptides bound to HLA-DQ8 - Mai T. Tran (Nature Portfolio, 2021)
Epitopes formed by fusion of more than one self peptide, such as proinsulin and other β cell proteins, can result in the formation of non-self hybrid peptides that can potentially trigger autoimmune responses. Here the authors show how TRBV5 + T cell receptors are geared towards recognition of HLA-DQ8 bound hybrid peptides in patients with type 1 diabetes.